Changes in the spectral characteristics of the liquid crystalline active medium doped with multi-walled carbon nanotubes under the influence of nitrogen dioxide - Kogut, I.; Mykytyuk, Z.; Kachurak, Y.; Vistak, M.; Blavt, O.; Kremer, I.; Shymchyshyn, O.; Tymkovich, R. (Physics and Chemistry of Solid State, 2025)
The paper examines the effect of nitrogen dioxide (NO2) on the spectral characteristics of a liquid crystal mixture doped with multilayer nanotubes. The liquid crystal mixture was synthesized based on cholesteric liquid crystal BLO-61 and nematic 5CB (26%) with a wide range of mesophase existence temperatures, the concentration of nanotubes was up to 0.7%. It was established that the introduction of nanotubes into the mixture leads to a significant increase in the sensitivity of the mixture to inorganic substances due to increased absorption. An analysis of the change in the spectral properties of the mixture at different concentrations of nitrogen dioxide in the sensor volume was performed and the coefficient of spectral sensitivity was determined. The obtained results indicate the possible use of this mixture as a sensitive sensor element for the detection of nitrogen compounds in the future.